Efficacy of Transcranial Motor Evoked Potential Monitoring During Intra- and Extramedullary Spinal Cord Tumor Surgery: A Prospective Multicenter Study of the Monitoring Committee of the Japanese Society for Spine Surgery and Related Research. Issue 4 (May 2023) - Ushirozako, Hiroki; Yoshida, Go; Imagama, Shiro; Kobayashi, Kazuyoshi; Ando, Kei; Ando, Muneharu; Kawabata, Shigenori; Yamada, Kei; Kanchiku, Tsukasa; Fujiwara, Yasushi; Taniguchi, Shinichirou; Iwasaki, Hiroshi; et al.
Study Design: Multicenter prospective study. Objectives: Although intramedullary spinal cord tumor (IMSCT) and extramedullary SCT (EMSCT) surgeries carry high risk of intraoperative motor deficits (MDs), the benefits of transcranial motor evoked potential (TcMEP) monitoring are well-accepted; however, comparisons have not yet been conducted. This study aimed to clarify the efficacy of TcMEP monitoring during IMSCT and EMSCT resection surgeries. Methods: We prospectively reviewed TcMEP monitoring data of 81 consecutive IMSCT and 347 EMSCT patients. We compared the efficacy of interventions based on TcMEP alerts in the IMSCT and EMSCT groups. We defined our alert point as a TcMEP amplitude reduction of ≥70% from baseline. Results: In the IMSCT group, TcMEP monitoring revealed 20 true-positive (25%), 8 rescue (10%; rescue rate 29%), 10 false-positive, a false-negative, and 41 true-negative patients, resulting in a sensitivity of 95% and a specificity of 80%. In the EMSCT group, TcMEP monitoring revealed 20 true-positive (6%), 24 rescue (7%; rescue rate 55%), 29 false-positive, 2 false-negative, and 263 true-negative patients, resulting in a sensitivity of 91% and specificity of 90%. The most common TcMEP alert timing was during tumor resection (96% vs. 91%), and suspension surgeries with or without intravenous steroid administration were performed as intervention techniques. Conclusions: Postoperative MD rates in IMSCT and EMSCT surgeries using TcMEP monitoring were 25% and 6%, and rescue rates were 29% and 55%. We believe that the usage of TcMEP monitoring and appropriate intervention techniques during SCT surgeries might have predicted and prevented the occurrence of intraoperative MDs.